2018
DOI: 10.1111/imr.12688
|View full text |Cite
|
Sign up to set email alerts
|

Virus dynamics and phyloanatomy: Merging population dynamic and phylogenetic approaches

Abstract: In evolutionary biology and epidemiology, phylodynamic methods are widely used to infer population biological characteristics, such as the rates of replication, death, migration, or, in the epidemiological context, pathogen spread. More recently, these methods have been used to elucidate the dynamics of viruses within their hosts. Especially the application of phylogeographic approaches has the potential to shed light on anatomical colonization pathways and the exchange of viruses between distinct anatomical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 131 publications
0
13
0
1
Order By: Relevance
“…This observation highlights the need to carefully assess the validity of phylogenetic methods that rely on the assumption of neutral evolution when analyzing within-host evolution of HIV-1, in particular phyloanatomic analyses (Salemi and Rife 2016; Lorenzo-Redondo et al. 2016; Bons and Regoes 2018). We also provide insights into how viral population sequencing data can be used to alleviate problems of phylogenetic reconstruction and analyze sequence diversity to predict evolutionary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This observation highlights the need to carefully assess the validity of phylogenetic methods that rely on the assumption of neutral evolution when analyzing within-host evolution of HIV-1, in particular phyloanatomic analyses (Salemi and Rife 2016; Lorenzo-Redondo et al. 2016; Bons and Regoes 2018). We also provide insights into how viral population sequencing data can be used to alleviate problems of phylogenetic reconstruction and analyze sequence diversity to predict evolutionary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We purposely chose this experimental design to control for the variation expected if experimentally or naturally infected animals were used, in order to establish a technical protocol for intrahost phylogenetic studies. This allowed us to determine, without bias, the best methods for obtaining consistent virus RNA for downstream sequencing experiments to contribute to the newly emerging field of phyloanatomy (34, 35). In both natural and experimental infection, several publications have demonstrated that WNV infection in the equine brain and spinal cord is multifocal (1417).…”
Section: Discussionmentioning
confidence: 99%
“…We incorporated PCR into this protocol because prior literature indicates inconsistent results in sequencing output in the face of positive real time rtPCR results in equine WNV infection (35). This is especially important for WNV disease in horses where virus is highly variable regionally in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…This tripartite interplay is referred to as G*G*E interactions in ecology and evolution, while epidemiologists often pinpoint individual edges in this interaction network and refer to them as cofactors. Third, the notion of 'environment' for a viral infection must be understood as a Russian-doll hierarchical integration across levels, from the virocell to the ecology: cell type diversity may display different permissivity to the infection and different potential for malignization (in the case of HPV, see [8]); tissue diversity may differentially foster malignancy [9]; organ diversity may introduce within-patient structuring of the viral population [10]; individual behaviour may strongly impact viral circulation; biological and physico-chemical agents may modify the host-pathogen interaction; and human population structure will undoubtedly pattern viral population structure. In summary, to understand DNA oncovirus virulence, it is necessary to adopt a multi-scale approach and bridge the cellular and the population levels.…”
Section: Dna Oncoviruses: Low Infection Virulence and High Disease Bumentioning
confidence: 99%